Symbolic capital of Slovenian reading - Blatnik, Andrej (Družboslovne razprave, 2012)
Following the idea of various capitals in the publishing field established by John B. Thompson, we can observe the book consumption as a process where an investment of economic capital in a bought book results in the potential growth of intellectual and symbolic capital gained by reading. The article is exploring the approach to these book capitals in Slovenia on the ground of a research carried out in 2010 and 2011, comparing its results with those of previous book researches, especially in connection with some specifics of the Slovenian book field such as strong system of public libraries and accordingly low number of books being sold in the bookstores.
Keywords: branje; bralna kultura; bralne navade; knjižni trg; simbolni kapital; Slovenia; Slovenija